2007
DOI: 10.1128/jvi.00513-07
|View full text |Cite
|
Sign up to set email alerts
|

CD163 Expression Confers Susceptibility to Porcine Reproductive and Respiratory Syndrome Viruses

Abstract: Direct functional screening of a cDNA expression library derived from primary porcine alveolar macrophages (PAM) revealed that CD163 is capable of conferring a porcine reproductive and respiratory syndrome virus (PRRSV)-permissive phenotype when introduced into nonpermissive cells. Transient-transfection experiments showed that full-length CD163 cDNAs from PAM, human U937 cells (histiocytic lymphoma), African green monkey kidney cells (MARC-145 and Vero), primary mouse peritoneal macrophages, and canine DH82 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
244
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(251 citation statements)
references
References 34 publications
5
244
2
Order By: Relevance
“…Most likely, endosomal acidification activates proteases such as cathepsin E or other serine proteases, which are involved in the uncoating of PRRSV. In addition, transient transfection of CD163 was shown to enable PRRSV replication in non-susceptible cells and CD163 antibodies were shown to interfere with infection of Marc-145 cells [6]. These results suggests that besides a critical role of CD163 in PRRSV entry in Marc-145 cells, this molecule might also be involved in PRRSV entry in macrophages, however this needs to be addressed in more detail in studies with primary macrophages.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Most likely, endosomal acidification activates proteases such as cathepsin E or other serine proteases, which are involved in the uncoating of PRRSV. In addition, transient transfection of CD163 was shown to enable PRRSV replication in non-susceptible cells and CD163 antibodies were shown to interfere with infection of Marc-145 cells [6]. These results suggests that besides a critical role of CD163 in PRRSV entry in Marc-145 cells, this molecule might also be involved in PRRSV entry in macrophages, however this needs to be addressed in more detail in studies with primary macrophages.…”
Section: Discussionmentioning
confidence: 94%
“…Attachment of PRRSV to sialoadhesin is mediated by sialic acids present on the surface of PRRS virions [14,16]. CD163, a cellular protein in the scavenger receptor cysteine-rich superfamily, has recently been shown also to function as a PRRSV receptor in Marc-145 cells, but its role in PRRSV infection of primary macrophages has not been studied [6].…”
Section: Introductionmentioning
confidence: 99%
“…This receptor is restricted to cells of the porcine monocyte/macrophage lineage and more specifically, to macrophages and tissue DC [53] and confers susceptibility to PRRSV [43]. CD163…”
Section: Cd163mentioning
confidence: 99%
“…Signaling through CD163 can, in turn, lead to the secretion of high levels of IL-10 in macrophages, resulting in a positive feedback loop (Philippidis et al, 2004). In this respect, the interaction of PRRSV with CD163 recently reported by Calvert et al (2007) might play a role in the increased levels of IL-10 in PRRS.…”
Section: Discussionmentioning
confidence: 99%
“…In swine, we reported a role for CD163 in African swine fever (ASF) virus infection of monocyte/macrophage (Sánchez-Torres et al, 2003). Recently, Calvert et al (2007) have shown that expression of CD163 made cells susceptible to porcine respiratory and reproductive syndrome (PRRS) virus infection.…”
Section: Discussionmentioning
confidence: 99%